Desempenho motor de aluno com paralisia cerebral discinética frente à adaptação das propriedades físicas de recurso pedagógico - Gonçalves, Adriana Garcia [UNESP]; Braccialli, Lígia Maria Presumido [UNESP]; Carvalho, Sebastião Marcos Ribeiro de [UNESP] (FapUNIFESP (SciELO), 2013)
The main purpose of this study was to analyze the modified physical properties of an educational resource for facilitating the handling of a child with dyskinetic cerebral palsy. The participant of the study was a six year old child with dyskinetic cerebral palsy enrolled in a regular early childhood education classroom. The educational resource that was selected was a brick game, in which the physical properties of weight, size and texture had been modified. The analysis was made regarding the quality of upper limb movement to the variables: righting index, scalar displacement (s), average speed (As) and time (t). The results showed that combined large size and heavy weight did not have a satisfactory outcome, affecting both grasping the educational resource and fitting. There was also inconsistency in children with cerebral palsy's responses. There is variation in the results, though a standard cannot be established. Thus, this study contributed to understanding the motor responses of a child with dyskinetic cerebral palsy when participating in a fitting activity with educational resources in which the physical properties had been modified.
Motor performance of students with dyskinetic cerebral palsy and the adaptation of physical properties of educacional resources
Keywords: Cerebral palsy; Educational resource; Special education